The Influence of Competence and Organizational Culture on Teacher Performance in SMK Negeri 1 Rawajitu Selatan Tulang Bawang - Susanto, Agus; Ahmaluddin, Ahmaluddin (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
This study analyzed the influence of competence and organizational culture on teacher performance at SMK Negeri 1 Rawajitu Selatan, Tulang Bawang. Teacher competence and organizational culture were considered essential factors affecting performance in the educational environment. A quantitative approach with a survey method was applied, and data were collected through questionnaires distributed to the teachers. Multiple linear regression analysis was used to examine the relationship between competence, organizational culture, and teacher performance. The results indicated that both teacher competence and organizational culture significantly influenced teacher performance. Competence contributed to enhancing the quality of teaching and learning, while a positive organizational culture supported collaboration, effective communication, and the development of teacher professionalism. These findings suggested that strengthening teacher competence and fostering a conducive organizational culture could serve as effective strategies for improving teacher performance. The study was expected to contribute to the development of educational policies and school management practices, particularly in efforts to enhance teacher quality and establish a productive work culture. Additionally, the results could serve as a reference for schools with similar contexts in improving the performance of their teaching staff.